Health in All Policies at the Local Level: What Facilitates Success?; Comment on "A Realist Explanatory Case Study Investigating How Common Goals, Leadership, and Committed Staff Facilitate Health in All Policies Implementation in the Municipality of Kuopio, Finland" - Carmel Williams; Nicole Valentine (Kerman University of Medical Sciences, 2023)
The paper by Guglielmin and colleagues1 examines the implementation of Health in All Policies (HiAP) in a local government context in Kuopio Finland. The authors use a realist explanatory case study design to explore what has supported HiAP implementation with a focus on two specific hypotheses on what leads to success: common goals and committed leadership and staff. The paper is well argued using appropriate methodology and their findings support the importance of the success factors tested by their two hypotheses. However, the narrowed focus on just two hypotheses underrepresents the complexity of implementing HiAP at any level of government, including local government. Given its local government focus, the paper would have been strengthened by referencing the lessons gained from the Healthy Cities movement. Local government is a critical setting for action to address health and health equity and there is great potential to continue research that adds to the knowledge base on how to successful implement HiAP. Finally, it is important to acknowledge that Finland has a unique HiAP history. It is recognised as a global leader in the field, and the role of local government in Finland differs from many other countries. These factors may impact on the transferability of the case study findings.